Euclid preparation: XXX. Performance assessment of the NISP red grism through spectroscopic simulations for the wide and deep surveys - Gabarra L.; Mancini C.; Rodriguez Muñoz L.; Rodighiero G.; Sirignano C.; Scodeggio M.; Talia M.; Dusini S.; Gillard W.; Granett B.R.; Maiorano E.; Moresco M.; et al. (EDP Sciences, 2025)
This work focusses on the pilot run of a simulation campaign aimed at investigating the spectroscopic capabilities of the Euclid Near-Infrared Spectrometer and Photometer (NISP), in terms of continuum and emission line detection in the context of galaxy evolutionary studies. To this purpose, we constructed, emulated, and analysed the spectra of 4992 star-forming galaxies at 0.3 ≤ z ≤ 2.5 using the NISP pixel-level simulator. We built the spectral library starting from public multi-wavelength galaxy catalogues, with value-added information on spectral energy distribution (SED) fitting results, and stellar population templates from Bruzual & Charlot (2003, MNRAS, 344, 1000). Rest-frame optical and near-IR nebular emission lines were included using empirical and theoretical relations. Dust attenuation was treated using the Calzetti extinction law accounting for the differential attenuation in line-emitting regions with respect to the stellar continuum. The NISP simulator was configured including instrumental and astrophysical sources of noise such as the dark current, read-out noise, zodiacal background, and out-of-field stray light. In this preliminary study, we avoided contamination due to the overlap of the slitless spectra. For this purpose, we located the galaxies on a grid and simulated only the first order spectra. We inferred the 3.5σ NISP red grism spectroscopic detection limit of the continuum measured in the H band for star-forming galaxies with a median disk half-light radius of 0.″4 at magnitude H = 19.5 ± 0.2 AB mag for the Euclid Wide Survey and at H = 20.8 ± 0.6 AB mag for the Euclid Deep Survey. We found a very good agreement with the red grism emission line detection limit requirement for the Wide and Deep surveys. We characterised the effect of the galaxy shape on the detection capability of the red grism and highlighted the degradation of the quality of the extracted spectra as the disk size increased. In particular, we found that the extracted emission line signal-to-noise ratio (S/N) drops by ~45% when the disk size ranges from 0.″25 to 1″. These trends lead to a correlation between the emission line S/N and the stellar mass of the galaxy and we demonstrate the effect in a stacking analysis unveiling emission lines otherwise too faint to detect.
Key words: surveys / Galaxy: evolution / galaxies: formation / galaxies: star formation / techniques: spectroscopic / instrumentation: detectors